Resources, services and risks : how can data observatories bridge the science-policy divide in environmental governance? /: how can data observatories bridge the science-policy divide in environmental governance?. (2016) - Kurian, Mathew; Ardakanian, Reza; Veiga, Linda Gonçalves; Meyer, Kristin
No abstract available